Uji validitas dan reliabilitas kuesioner Tingkat pemahaman obstructive sleep apnea (osa) dokter gigi di jakarta - Zakiyah Karim, Tasya; Chandra Dwidjayanti, Siti; Seftiana Indah Sari, Eka (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Obstructive Sleep Apnea (OSA) is a sleep disorder characterized by breathing difficulties during sleep. Dentists play a crucial role in raising awareness about OSA and assisting patients in obtaining a diagnosis by providing accurate information. This necessitates using precise measurement tools to identify and assess sleep disorders in patients during dental visits. Objective: To determine the validity and reliability of a questionnaire regarding dentists' understanding of Obstructive Sleep Apnea (OSA) in Jakarta. Method: This study employed an analytical observational approach using a cross-sectional design. The sample included 220 dentists working in Jakarta's health centers, clinics, and hospitals. Data analysis was conducted using the Kolmogorov-Smirnov Test for normality test. Results: The correlation test results indicated that the questionnaire met the criteria for validity. The average Cronbach's Alpha value was 0.712, exceeding the minimum value of 0.60, indicating that the questionnaire used in this study is reliable and can accurately measure dentists' understanding of OSA. Conclusion: Research involving dentists aged 25-50 suggests that the questionnaire assessing the level of knowledge of Obstructive Sleep Apnea (OSA) demonstrates good accuracy and can be relied upon as a tool to evaluate dentists' comprehension of OSA.